Considering Non-Dichotomous Global-Oriented Educational Governance At Pondok Pesantren Bina Insan Mulia Cirebon - Gufron, Iffan Ahmad; Barnawi, Barnawi; Hardiansyah, Bilal (Balai Diklat Keagamaan Bandung, 2024)
This paper aims to describe the non-dichotomous educational governance with a global perspective at Pondok Pesantren Bina Insan Mulia Cirebon. The research employs a descriptive method, gathering data through interviews with the director and teaching staff. Data analysis involved reduction, display, and conclusion drawing stages. Findings indicate the strategic potential of the pesantren in reforming and modernizing governance due to visionary leadership, a strong tradition, its role as a center for education and thought, and financial independence. The implementation of transformation strategies towards non-dichotomous education is achieved through elective programs, mandatory programs, and life schools; foreign language-based globalization; integrated learning and orientation; educator training; cultural acculturation in education; non-dichotomous education; inclusive curriculum; pesantren rituals; and time management. In the evaluation phase, the pesantren establishes strict monitoring and evaluation mechanisms, performance indicators, achievement analysis, failure analysis, stakeholder involvement in evaluation, and renewal plan assessments.Keywords: Education; Governance; Islamic boarding school; Nondichotomous